The combination of metformin and 2‐deoxyglucose significantly inhibits cyst formation in miniature pigs with polycystic kidney disease. (10th January 2019) - Lian, Xiaoying; Wu, Xiaoyuan; Li, Zhongxin; Zhang, Yingjie; Song, Kangkang; Cai, Guangyan; Li, Qinggang; Lin, Shupeng; Chen, Xiangmei; Bai, Xue‐Yuan
Abstract : Background and Purpose: The pathogenic mechanism of autosomal dominant polycystic kidney disease (ADPKD) is unclear. Similar to tumour cells, polycystic kidney cells are primarily dependent on aerobic glycolysis for ATP production. Compared with rodents, miniature pigs are more similar to humans. This study is the first time to investigate the effects of the combination of metformin and 2‐deoxyglucose (2DG) in a pig model of chronic progressive ADPKD. Experimental Approach: A miniature pig ADPKD model was established by inducible deletion of the PKD1 gene. Blood, urine and kidney biopsy specimens were collected for analysis at specific times. The renal vesicle index was analysed by three‐dimensional reconstruction of CT scans. Markers of the mammalian target of rapamycin (mTOR) and ERK signalling pathways and associated metabolism were detected by Western blots and colorimetry. Key Results: The three‐dimensional reconstruction of CT scans indicated a markedly lower renal vesicle index in the combination therapy group. Each drug intervention group showed a significantly lower serum creatinine and urinary protein/creatinine ratio. This treatment regimen also inhibited the activities of markers of the proliferation‐related mTOR and ERK pathways, and the expression of key enzymes involved in glycolysis, as well as reducing the production of ATP and lactic acid. Conclusions and Implications: This study showed that the combination of metformin and 2DG blocked the formation of renal cysts and improved the renal function in ADPKD miniature pigs. Our results indicate that the combination of metformin and 2DG may be a promising therapeutic strategy in human ADPKD.